Reversal of akinesia in experimental parkinsonism by GABA antagonist microinjections in the pedunculopontine nucleus - Nandi, D; Aziz, T; Giladi, N; Winter, J; Stein, J (2002)
Recent studies, mainly in animals, have shown that the pedunculopontine nucleus (PPN) in the upper brainstem has extensive connections with several motor centres in the CNS. This structure has also been implicated in the akinesia seen in patients with Parkinson's disease. Here we demonstrate that microinjection of γ-aminobutyric acid (GABA) receptor A antagonist substance, bicuculline, into the PPN of non-human primates (n = 2) rendered parkinsonian with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) results in significant improvement of akinesia. The effect of bicuculline microinjection in the PPN matches that of oral administration of L-dopa. This finding opens up new possibilities in the management of akinesia, the most intractable symptom of advanced Parkinson's disease.